The Effect of Food Price Fluctuations on Inflation After the 2024 General Election(Case Study: Medan City) - Fadhilah, Emma; Pulungan, Abraham Ismail; Depari, Nelfita Rizka S. (West Science Agro, 2025)
The city of Medan has several features that distinguish it from other cities in Indonesia. How fluctuations in food prices impact inflation can be influenced by variables such as the structure of the local food market, the accessibility of food distribution, and people's consumption patterns. The purpose of this research is to gain an understanding of the dynamics that occur in Medan, especially in the post-election context. This study aims to analyze the effect of food price fluctuations on the inflation rate in Medan City after the general election. Significant fluctuations in food prices often affect price stability and inflation, and the impact may become more complex after policy changes following the 2024 general election. This study aims to analyze the influence of food prices on inflation using a linear regression model with five independent variables: Rice Price, Chicken Meat Price, Red Chili Price, Beef Price, and Shallot Price. The Kolmogorov-Smirnov normality test on non-standardized residuals showed a significance value of 0.251, which is greater than 0.05, indicating normal distributed data. The histogram shows a distribution of data that deviates to the right, while the P-Plot test on standardized residual shows the absence of heteroscedasticity. The multicollinearity test with the Variance Inflation Factor (VIF) yielded values below 10.0 for all variables, indicating the absence of symptoms of multicollinearity. The results of the linear regression show that the coefficients for Rice Prices (-0.00000075), Red Chili Prices (-0.00000012), and Shallot Prices (-0.00000027) are negative, indicating an inverse relationship between these prices and inflation. Meanwhile, the coefficients for Chicken Meat Price (0.00000103) and Beef Price (0.00000008) were positive, but the effect was very small. A coefficient of determination (R²) of 0.609 indicates that about 60.9% of the variation in inflation can be explained by this model. The partial hypothesis test showed that only the Chicken Meat Price had a significant influence on inflation (significance value of 0.017, less than 0.05). The other variables did not show a significant influence because their significance value was greater than 0.05. The F test showed a significance value below 0.05, indicating that simultaneously, all five food price variables had a significant influence on inflation. The study concluded that, although only one variable was individually significant, overall, changes in food prices affected inflation.